If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 82 = -32 Reorder the terms: 82 + 6x = -32 Solving 82 + 6x = -32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-82' to each side of the equation. 82 + -82 + 6x = -32 + -82 Combine like terms: 82 + -82 = 0 0 + 6x = -32 + -82 6x = -32 + -82 Combine like terms: -32 + -82 = -114 6x = -114 Divide each side by '6'. x = -19 Simplifying x = -19
| 6x+16-15x=11 | | 3(m-17)=12 | | 0.25x+.05(14-x)=.10(-25) | | 2x+2=3x+4 | | 6+2q=3(q+2) | | 5-3*0+3= | | 4(5t-7)=10T+2 | | 6(f-5)=-30 | | a^2-x^2=0 | | (13w+7)(6w-18)=0 | | 3x+35=12x-64 | | -25=2x^2+30x | | 3x+5=4x+9 | | 12x^3-84x^2-120x=0 | | (7s+5)(2s-6)=0 | | 43-4X=5X+19 | | 3(2x-7)=3 | | 3.14=3.14xr^2 | | 12x^3+84x^2-120x=0 | | 4x+5=55 | | 3y+3y^2=9y | | 3x+30=12x-42 | | a-12+a+8=90 | | 7-9x=53-23x | | 5-r+8r=3r+1 | | m+3-5-3m+6+4m=5m+6+4m-3 | | 6n=6 | | -6*6= | | 13-8x=67-29x | | x+13=3(q+2)+2 | | 0.04x+.05(2-x)=.10(-6) | | -114-8x=7x+21 |